Design Model of Subak Smart Irrigation - Ananta Wijaya; Adisimakrisna Peling; I Gusti Ngurah Janardana (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2016)
Water has many benefits for human life. One of the benefits lies on the agricultural sector. However, as the water source is decreasing, the needs of water for agricultural sector is increasing. Subak is therefore one of the solutions in agricultural field. Meanwhile, the existence of subak also rises some problems. In terms of water source management, subak can be very effective. Unfortunately, subak is not that efficient in the water use. Smart irrigation with fuzzy logic used becomes a solution which has been offered to manage the water use based on the needs the paddy. This system uses solar panel and battery. In addition, it is completed by the weather censor and humidity. This system works during rice planting period. The findings show that the water irrigation on subak rice field becomes more effective, efficient and optimizing the harvest.